Jewish public culture in the late Russian empire - Veidlinger, Jeffrey, 1971- (Modern Jewish experience (Bloomington, Ind.), 2009)
In the midst of the violent, revolutionary turmoil that accompanied the last decade of tsarist rule in the Russian Empire, many Jews came to reject what they regarded as the apocalyptic and utopian prophecies of political dreamers and religious fanatics, preferring instead to focus on the promotion of cultural development in the present. Jewish Public Culture in the Late Russian Empire examines the cultural identities that Jews were creating and disseminating through voluntary associations such as librari.